IMPLEMENTATION OF MASLAHAH IN MODERN BUSINESS PRACTICES - Juni Iswanto; Mas'ut Mas'ut; Alfin Yuli Dianto (Program Studi Ekonomi Syariah, Institut Agama Islam Pangeran Diponegoro Nganjuk, 2021)
Islam is a religion that governs all aspects of life, including economics. The Islamic economy is an integral part of the teachings of Islam. All of his guidance and teachings aim to encourage all people to be safe both in this world and in the hereafter. In an increasingly advanced age, islamic teachings and guidance will still be relevant. Digitalization of business in the modern era, Islamic teachings should bring up a legal model in accordance with the principles of sharia economy. Keeping a modern business on the right path requires extra manpower for the culprit. Products sold, promotions, payment systems that do not violate religious prohibitions (riba, gharar, maysir and haram), become a new challenge for those who still maintain Maslahah. Nevertheless, the implementation of maslahah can continue to be maintained in accordance with the relevance of Islamic teachings in any era. Modern businesses (online businesses, Small Medium Enterprise, Startups) can continue to run profitable businesses, although it still maintains Islamic sharia as a foundation in the maslahah economy. But, the rampant practice of riba, illegal buying and selling, became a new problem for the establishment of the Islamic economy. Using studies to Islamic Entrepreneurs as a method of solving in order to stay upright maslahah can be the right choice.